Limit of DNA Barcode in delineating penaeus monodon and in its developing stages - Prasanna Kumar, C; Akbar John, B; Ajmal Khan, S; Lyla, P.S; Jalal, K.C.A (Universiti Kebangsaan Malaysia, 2012)
Mysis, post larvae and adult specimens of Penaeus monodon were sequenced for Cyctochrome C Oxidase subunit I (COI) gene (DNA barcode) to check the efficiency of DNA barcode in delineating species irrespective of its different life stages. COI gene sequences of different life stages of P. monodon were subjected to pair-wise distance analysis, nucleotide sequence diversity estimation, phylogenetic and BOLD analysis. The pair-wise distance estimation revealed that intra-specific variations within the barcode sequences of P. monodon were low when compared with other species of genus Penaeus spp. The average pair-wise distance within the sequences of different stages of P. monodon was two times lesser than the pair-wise distance of the out-group used. The nucleotide diversity within the barcodes were low (π = 0.324). The constructed phylogram clearly showed that the DNA barcoding using partial COI gene would provide an accurate delineation of species irrespective of their different life stages. The BOLD analysis accurately identified all sequences as belonging to P. monodon.